The Derivative Markets : structure, characteristics, and practice - Nwaobi, Godwin Chikwudum (Nigeria Quantitative Economic Research Bureau, 2009)
This book takes a prescriptive perspective and it is an up-to-date book, in terms of theoretical developments, empirical results and practical applications.
osc 18/7/16
Loan
Keywords: Derivatives; Derivatives market